GAMBARAN KARAKTERISTIK PERSALINAN PRETERM DAN BAYIBERATLAHIR RENDAH (BBLR) DI RSUD dr.R. GOETENG TAROENADIBRATA PURBALINGGA - Nurhasanah Nurhasanah; Wilis Sukmaningtyas (Universitas Harapan Bangsa Purwokerto, 2010)
Background : The infant mortality rate of 80 stillborn infants. Neonatal mortality and infantmortality as much as 115 infants aged <1 week as many as 96 babies. Infant mortality inPurbalingga, 32.17% due to LBW, preterm 31.3%, 14.7% of congenital anomalies, infection 0.8%and other factors as much as 20.8%. Health Department reports Descending (2010). Purpose : Knowing the characteristic picture of preterm delivery and low birth weightbabies in hospitals dr.R. Goeteng Taroenadibrata Purbalingga in 2010.Methods: This research method is purposive sampling is based on a sampling of certainconsiderations made by the researchers themselves, the study sample were all mothers ofpreterm birth in hospitals dr.R. Goeteng Taroenadibrata Purbalingga in 2010.Results : Characteristics based on maternal age on preterm delivery and low birthweight babies are not at risk as much as 90 respondents (77.6%) and are at risk as much as26 respondents (22.4%), from a distance of no-risk pregnancies as much as 76 respondents(65 , 5%) and are at risk as many as 40 respondents (34.5%), parity is not at risk of some 100respondents (86.2%) and are at risk as many as 16 respondents (13.8%).Conclusion : The image characteristics of preterm delivery and low birth weight babies inhospitals dr.R. Goeteng Taroenadibrata Purbalingga in 2010 fall into this category are notat risk.Key words : Preterm delivery, low birth weight babies.